Perkembangan Tarekat Naqsyabandiyah di Lubuak Landua Kabupaten Pasaman Barat Tahun 1990-2020 - Nadiarti Nadiarti; Abdul Salam (Jurusan Sejarah FIS UNP, 2022)
This study examines the development of the Naqsyabandiyah Order in Jorong Lubuk Landua, Pasaman Babrat Regency from 1990 to 2020. The research activity aims to determine the development and existence of the Naqsyabandiyah Order in the community, especially the Lubuak Landua community. This type of research is a qualitative research using historical research methods consisting of: heuristics, criticism, interpretation, and historiography. From the results of research activities, it can be seen that; (1). Lubuak Landua was the first area to become a center for the spread of Islam as well as a place where the teachings of the Naqsyabandiyah Order were developed. (2). The Naqshbandiyah Order is a mukhtabaroh order, because the worship recommended in this congregation is directly attributed to the Prophet Muhammad SAW. The development of the tarekat is inseparable from the Shaykh's efforts in broadcasting the knowledge of the tarekat so that it can be accepted by the community, even now the center of the teachings of the Naqsyabandiyah Order has been found in many areas in West Pasaman. (3). In a tarekat there are activities that become obligatory rituals, such as; Bai'at ceremony, practice of remembrance, implementation of suluk and khatam kawajangan.